Dynamic Color‐Switching of Plasmonic Nanoparticle Films. Issue 45 (30th September 2019) - Liu, Luntao; Aleisa, Rashed; Zhang, Yun; Feng, Ji; Zheng, Yiqun; Yin, Yadong; Wang, Wenshou
Abstract: The fast and reversible switching of plasmonic color holds great promise for many applications, while its realization has been mainly limited to solution phases, achieving solid‐state plasmonic color‐switching has remained a significant challenge owing to the lack of strategies in dynamically controlling the nanoparticle separation and their plasmonic coupling. Herein, we report a novel strategy to fabricate plasmonic color‐switchable silver nanoparticle (AgNP) films. Using poly(acrylic acid) (PAA) as the capping ligand and sodium borate as the salt, the borate hydrolyzes rapidly in response to moisture and produces OH − ions, which subsequently deprotonate the PAA on AgNPs, change the surface charge, and enable reversible tuning of the plasmonic coupling among adjacent AgNPs to exhibit plasmonic color‐switching. Such plasmonic films can be printed as high‐resolution invisible patterns, which can be readily revealed with high contrast by exposure to trace amounts of water vapor. Abstract : Color switching : Plasmonic color‐switchable silver nanoparticle (AgNP) films are prepared by integrating a humidity‐sensitive salt hydrolysis reaction with the charge‐dependent assembly/disassembly of AgNPs. The new AgNP film showed rapid and reversible plasmonic color‐switching with no noticeable decay of activity even after 1000 cycles.